Marvels of medicine : literature and scientific enquiry in early colonial Spanish America - Pérez Marín, Yarí (Liverpool Latin American studies, 2020)
"Marvels of Medicine makes a compelling case for including sixteenth century medical and surgical writing in the critical frameworks we now use to think about a genealogy of cultural expression in Latin America. Focusing on a small group of practitioners who differed in their levels of training, but who shared the common experience of having left Spain to join colonial societies in the making, this book analyses the paths their texts charted to attitudes and political positions that would come to characterize a criollo mode of enunciation. Unlike the accounts of first explorers, which sought to amaze audiences back in Europe with descriptions of strange and astonishing lands, these texts instead engaged the marvellous in an effort to supersede it, stressing the value of sensorial experience and of verifying information thorough repetition and demonstration. Vernacular medical writing became an unlikely early platform for a new form of regionally anchored discourse that demanded participation in a global intellectual conversation, yet found itself increasingly relegated to the margins. In responding to that challenge, anatomical treatises, natural histories and surgical manuals exceeded the bounds set by earlier templates becoming rich, hybrid narratives that were as concerned with science as with portraying the lives and sensibilities of women and men in early colonial Mexico." --